2020
DOI: 10.1016/j.chom.2020.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic Analysis of the Interaction between Clostridioides difficile Infection and Pediatric Inflammatory Bowel Disease

Abstract: Highlights d Multi-omics reveals markers of CDI in pediatric IBD patients d Identification of metabolites reveals distinctive features for IBD and CDI d Isocaproyltaurine is made by C. difficile and associates with active IBD d Identifies biomarkers potentially useful for distinguishing disease processes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 83 publications
4
51
0
Order By: Relevance
“…Of interest, it has been recently reported that succinate levels are increased in stool samples of paediatric CD patients infected with Clostridioides difficile compared with paediatric CD patients without infection. In this elegant study, the authors associate for the first time a metabolomic alteration with a specific bacterium [20]. In line with this, it has also been recently reported that succinate levels of intestinal aspirates from paediatric IBD patients positively correlates with the invasion of Escherichia Coli [21].…”
Section: Metabolite Alterationsupporting
confidence: 55%
“…Of interest, it has been recently reported that succinate levels are increased in stool samples of paediatric CD patients infected with Clostridioides difficile compared with paediatric CD patients without infection. In this elegant study, the authors associate for the first time a metabolomic alteration with a specific bacterium [20]. In line with this, it has also been recently reported that succinate levels of intestinal aspirates from paediatric IBD patients positively correlates with the invasion of Escherichia Coli [21].…”
Section: Metabolite Alterationsupporting
confidence: 55%
“…Interestingly, one strain of an unnamed Clostridium bacterium capable of deconjugation shows increased growth when taurine was added to the growth medium, indicating that BSH activity might be nutritionally beneficial [48]. Taurine is also enriched in the feces of pediatric inflammatory bowel disease patients with CDI, indicating a potential association between C. difficile and taurine [49].…”
Section: Bile Salt Hydrolasesmentioning
confidence: 99%
“…There are seven example workflows provided in iMAP. They were summarized from published metabolomic studies with different strategies for key metabolites selection, pathway analysis, and/or predictive model building (Sreekumar et al, 2009 ; Liu et al, 2019 ; Bushman et al, 2020 ). It's convenient to construct customized workflows by modifying these example workflows.…”
Section: Methodsmentioning
confidence: 99%